2004
DOI: 10.1002/art.20580
|View full text |Cite
|
Sign up to set email alerts
|

Expression of mitogen‐activated protein kinase phosphatase 1, a negative regulator of the mitogen‐activated protein kinases, in rheumatoid arthritis: Up‐regulation by interleukin‐1β and glucocorticoids

Abstract: Mitogen-activated protein kinases (MAPKs) are key components of intracellular signal transduction pathways that relay extracellular signals to the cell nucleus to activate transcription of genes involved in inflammation, cell migration, cell-cycle control, and apoptosis (1). The MAPKs are induced by proinflammatory cytokines such as tumor necrosis factor ␣ (TNF␣), interleukin-1␤ (IL-1␤), and macrophage migration inhibitory factor (MIF), and by growth factors and mediators of cellular stress, and regulate the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 45 publications
4
44
2
Order By: Relevance
“…Previous investigators have used MKP-1 inhibitors, such as Ro-31-8220 and triptolide, to investigate the role of MKP-1 (21,28,29); however, we found that these inhibitors were toxic to ASMC in culture and, in addition, these inhibitors were unlikely to be selective for MKP-1. For example, Ro-31-8220 is an inhibitor of protein kinase C and raf-1, although it is claimed that this compound inhibits MKP-1 expression independent of these effects in different cell types (30,31).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Previous investigators have used MKP-1 inhibitors, such as Ro-31-8220 and triptolide, to investigate the role of MKP-1 (21,28,29); however, we found that these inhibitors were toxic to ASMC in culture and, in addition, these inhibitors were unlikely to be selective for MKP-1. For example, Ro-31-8220 is an inhibitor of protein kinase C and raf-1, although it is claimed that this compound inhibits MKP-1 expression independent of these effects in different cell types (30,31).…”
Section: Discussionmentioning
confidence: 57%
“…For example, Ro-31-8220 is an inhibitor of protein kinase C and raf-1, although it is claimed that this compound inhibits MKP-1 expression independent of these effects in different cell types (30,31). The studies using these inhibitors demonstrate that MKP-1 is a critical negative regulator of the release of inflammatory cytokines from murine macrophages or synoviocytes (21,28,29). Using MKP-1 Ϫ/Ϫ macrophages, Zhao et al (32) demonstrated that these murine cells produce more TNF-␣, IL-6, and IL-10 when challenged with LPS compared with wild-type macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting was performed as previously described (Toh et al, 2004;Yang et al, 2013b). Briefly, cell lysates were collected using cell lysis buffer supplemented with complete mini protease inhibitor cocktail.…”
Section: Western Blottingmentioning
confidence: 99%
“…It is expressed in response to GCs A Clark Anti-inflammatory functions of glucocorticoid-induced genes Page 18 of 53 in a wide variety of cell types including mast cells (Kassel et al, 2001), monocytes or macrophages (Abraham et al, 2006;Aeberli et al, 2006;Bhattacharyya et al, 2007;Chen et al, 2002;Zhao et al, 2005), microglia (Zhou et al, 2007), T lymphocytes , dermal, lung and synovial fibroblasts (Phillips et al, 2006;Toh et al, 2004;Yang et al, 2006), endothelial cells (Furst et al, 2007), osteoblasts (Engelbrecht et al, 2003;Leclerc et al, 2004), keratinocytes (Onda et al, 2006;Stojadinovic et al, 2006), adipocytes (Bazuine et al, 2004), lung epithelial cells (Chivers et al, 2006;Hermoso et al, 2004), airway smooth muscle cells (Issa et al, 2007) and HeLa cells (Imasato et al, 2002;Lasa et al, 2002). Typically expression is quite rapid (within one hour), sustained (up to 24 hours), requires relatively low concentrations of GC, and is blocked by the GR antagonist RU486.…”
Section: Dusp1mentioning
confidence: 99%